Find integral x2 + x + 1 dx / (x + 2) (x2 + 1)

Examples

Example 1 (ii)

Example 1 (iii)

Example 2 (i)

Example 2 (ii)

Example 2 (iii) Important

Example 3 (i)

Example 3 (ii) Important

Example 3 (iii)

Example 4

Example 5 (i)

Example 5 (ii)

Example 5 (iii) Important

Example 5 (iv) Important

Example 6 (i)

Example 6 (ii) Important

Example 6 (iii) Important

Example 7 (i)

Example 7 (ii) Important

Example 7 (iii)

Example 8 (i)

Example 8 (ii) Important

Example 9 (i)

Example 9 (ii) Important

Example 9 (iii) Important

Example 10 (i)

Example 10 (ii) Important

Example 11

Example 12

Example 13 Important

Example 14

Example 15 Important

Example 16 Important You are here

Example 17

Example 18 Important

Example 19

Example 20 Important

Example 21 Important

Example 22 Important

Example 23

Example 24

Example 25 (i)

Example 25 (ii) Important

Example 25 (iii)

Example 25 (iv) Important

Example 26

Example 27

Example 28 Important

Example 29

Example 30

Example 31

Example 32 Important

Example 33 Important

Example 34 Important

Example 35

Example 36 Important

Example 37 Important

Example 38 Important

Example 39 Important

Example 40 Important

Example 41 Important

Example 42 Important

Question 1 Important Deleted for CBSE Board 2024 Exams

Question 2 Deleted for CBSE Board 2024 Exams

Question 3 (Supplementary NCERT) Important Deleted for CBSE Board 2024 Exams

Last updated at May 29, 2023 by Teachoo

Example 16 Find ∫1▒(𝑥^2+ 𝑥 +1 𝑑𝑥 )/((𝑥 + 2) (𝑥^2+1) ) We can write equation as (𝑥^2+ 𝑥 + 1)/((𝑥 + 1) (𝑥 + 2) )=𝐴/(𝑥 + 2) + (𝐵𝑥 + 𝐶)/(𝑥^2+ 1) Cancelling denominator 〖 𝑥〗^2+ 𝑥+1=𝐴(𝑥^2+1)+(𝐵𝑥+𝐶) (𝑥+2) Putting x = −𝟐 (−2)^2+(−2)+1=𝐴((−2)^2+1)+0 4−2+1= 5A 3/5 = A Putting x = 𝟎 𝑥^2+ 𝑥+1=𝐴(𝑥^2+1)+(𝐵𝑥+𝐶) (𝑥+2) 0+0+0= A(0 + 1) + (0 + C) (0 + 2) 1 = A + 2C 1 = 3/5 + 2C 1 – 3/5 = 2C 2/5 = 2C C = 1/5 Putting x = 1 𝑥^2+ 𝑥+1=𝐴(𝑥^2+1)+(𝐵𝑥+𝐶) (𝑥+2) 1+1+1= 2A + (B + C)(3) 3 = 2A + 3 (B + C) 3 = 2(3/5) + 3 (B+1/5) 3 – 6/5 = 3 (B+1/5) 9/5 = 3 (B+1/5) 3/5 – 1/5 = B B = 2/5 Thus, (𝑥^2+ 𝑥 + 1)/((𝑥 + 1) (𝑥 + 2) )=𝐴/(𝑥 + 2) + (𝐵𝑥 + 𝐶)/(𝑥^2+ 1) (𝑥^2+ 𝑥 + 1)/((𝑥 + 1)(𝑥^2+ 1)) = 3/(5 (𝑥 + 2)) + (1 (2𝑥 + 1))/(5 (𝑥^2 + 1)) Hence, our equation becomes ∫1▒(𝑥^2+ 𝑥 + 1)/((𝑥 + 2) (𝑥^2 + 1)) 𝑑𝑥= ∫1▒3/(5(𝑥^2 + 1)) 𝑑𝑥+∫1▒1/5 ((2𝑥 + 1))/(𝑥^2 + 1) 𝑑𝑥 = ∫1▒3/(5(𝑥^2 + 1)) 𝑑𝑥+ 1/5 ∫1▒〖2𝑥/(𝑥^2 + 1) 𝑑𝑥+〗 1/5 ∫1▒1/(𝑥^2 + 1) 𝑑𝑥 𝐈𝟐 1/5 ∫1▒2𝑥/(𝑥^2+ 1) 𝑑𝑥 Let 𝑡=𝑥^2+ 1 𝑑𝑡/𝑑𝑥=2𝑥 𝑑𝑡=2𝑥 𝑑𝑥 Substituting, =1/5 ∫1▒𝑑𝑡/𝑡 = 1/5 log |𝑡| + C_2 = 1/5 log |𝑥^2+1| + C_2 𝐈𝟑 1/5 ∫1▒1/(𝑥^2+ 1) 𝑑𝑥 = 1/5 〖𝑡𝑎𝑛〗^(−1) (𝑥)+C_3 Hence ∫1▒(𝑥^2+ 𝑥 + 1)/((𝑥 + 2) (𝑥^2+ 1)) 𝑑𝑥 =𝟑/𝟓 𝒍𝒐𝒈|𝒙+𝟐|+𝟏/𝟓 𝒍𝒐𝒈|𝒙^𝟐+𝟏|+𝟏/𝟓 〖𝒕𝒂𝒏〗^(−𝟏) (𝒙)+ C where C = C_1+ C_2+C_3

You are watching: Find integral x2 + x + 1 dx / (x + 2) (x2 + 1). Info created by THVinhTuy selection and synthesis along with other related topics.

Rate this post